China's global disruption : myths and reality - Lo, Chi (Emerald Publishing Limited, 2021)
Those who study China's domestic economics tend to focus on its businesses, industries, supply chains, and energy market disruption through anecdotal case studies, which often point to impending collapse. This hardly squares with the domit views of international relations scholarship, much of which focuses on system-level analyses and tends to predict that China will inevitably achieve ever-greater global power. It is no wonder that so many long-held assumptions about China have an air of paradox to them. Here Chi Lo presents the first full-length study to bring systemic analyses into dialog with domestic analyses, and in so doing, to show how each can challenge or refine the assumptions of the other. Taking on key presuppositions about the resilience (or otherwise) of China's economic fundamentals, and explaining why much of the global "common sense" about China is misinformed, this book applies evidence-based research to provide a novel picture of China's development and its place within the global economic system. China's Global Disruption: Myths and Reality is a must-read for students and researchers in both international studies and economics, and it is of keen interest to policymakers and practitioners concerned with China's ever-evolving place within the international political economy.